Seed longevity of maize conserved under germplasm bank conditions for up to 60 years. (13th February 2021) - Guzzon, Filippo; Gianella, Maraeva; Velazquez Juarez, Jose Alejandro; Sanchez Cano, Cesar; Costich, Denise E
Abstract: Background and Aims: The long-term conservation of seeds of plant genetic resources is of key importance for food security and preservation of agrobiodiversity. Nevertheless, there is scarce information available about seed longevity of many crops under germplasm bank conditions. Methods: Through germination experiments as well as the analysis of historical monitoring data, we studied the decline in viability manifested by 1000 maize ( Zea mays subsp. mays ) seed accessions conserved for an average of 48 years at the CIMMYT germplasm bank, the largest maize seedbank in the world, under two cold storage conditions: an active (–3 °C; intended for seed distribution) and a base conservation chamber (–15 °C; for long-term conservation). Key Results: Seed lots stored in the active chamber had a significantly lower and more variable seed germination, averaging 81.4 %, as compared with the seed lots conserved in the base chamber, averaging 92.1 %. The average seed viability detected in this study was higher in comparison with that found in other seed longevity studies on maize conserved under similar conditions. A significant difference was detected in seed germination and longevity estimates (e.g. p85 and p50 ) among accessions. Correlating seed longevity with seed traits and passport data, grain type showed the strongest correlation, with flint varieties being longer lived than floury and dent types. Conclusions: The more rapid loss of seed viability detected in the active chamber suggests that the seed conservation approach, based on the storage of the same seed accessions in two chambers with different temperatures, might be counterproductive for overall long-term conservation and that base conditions should be applied in both. The significant differences detected in seed longevity among accessions underscores that different viability monitoring and regeneration intervals should be applied to groups of accessions showing different longevity profiles.